2008
DOI: 10.4062/biomolther.2008.16.2.069
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Actions of Lysophosphatidylcholine

Abstract: − Lysophosphatidylcholine (LPC) is an endogenous phospholipid. LPC has various stimulating or modulating activities on immune cells, including lymphocytes, monocytes/macrophages and neutrophils. Studies generally revealed pro-inflammatory activities of LPC, but accumulating evidence indicates that LPC has also anti-inflammatory actions. Here we summarize immunomodulatory actions of LPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 65 publications
(133 reference statements)
0
6
0
Order By: Relevance
“…Lysophosphatidylcholine can recruit immune cells and modulate their function, especially in neutrophils and T cells, and it may play a role in the control of bacterial growth during infection ( 28 ). To verify whether LPC possesses mycobactericidal activity, mouse macrophages were infected with avirulent or virulent Mtb, H37Ra or H37Rv, respectively, at an MOI of 0.1 or 1 and then treated them with LPC (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysophosphatidylcholine can recruit immune cells and modulate their function, especially in neutrophils and T cells, and it may play a role in the control of bacterial growth during infection ( 28 ). To verify whether LPC possesses mycobactericidal activity, mouse macrophages were infected with avirulent or virulent Mtb, H37Ra or H37Rv, respectively, at an MOI of 0.1 or 1 and then treated them with LPC (Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lysophosphatidylcholine, an endogenous phospholipid, has various stimulating or modulating effects on immune cells, such as monocytes/macrophages, neutrophils, and lymphocytes ( 28 ). Most studies have demonstrated pro-inflammatory activities of LPC; however, LPC possesses anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes/macrophages are the prime immune cells managing inflammatory responses, which contribute to development of number of diseases such as cancer, diabetes, and atherosclerosis [ 30 , 31 ]. This view led us to develop novel immunoregulatory drugs based on the functional activation of monocytes and macrophages without side effects to prevent such diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Under inflammatory conditions, LPCs can be generated by reactive oxygen species (ROS) . Some type of LPCs can release highly unsaturated arachidonic acid that is readily converted into compounds with either pro‐ or anti‐inflammatory effects . Downregulation of LPCs may reflect disturbed inflammation in ONFH.…”
Section: Discussionmentioning
confidence: 99%